Estimating Impacts and Trade‐offs in Solar Geoengineering Scenarios With a Moist Energy Balance Model. Issue 9 (8th May 2020) - Lutsko, Nicholas J.; Seeley, Jacob T.; Keith, David W.
Abstract: There are large uncertainties in the potential impacts of solar radiation modification (SRM) and in how these impacts depend on the way SRM is deployed. One open question concerns trade‐offs between latitudinal profiles of insolation reduction and climate response. Here, a moist energy balance model is used to evaluate several SRM proposals, providing fundamental insight into how the insolation reduction profile affects the climate response. The optimal SRM profile is found to depend on the intensity of the intervention, as the most effective profile for moderate SRM focuses the reduction at high latitudes, whereas the most effective profile for strong SRM is tropically amplified. The effectiveness of SRM is also shown to depend on when it is applied, an important factor to consider when designing SRM proposals. Using an energy balance model allows us to provide physical explanations for these results while also suggesting future avenues of research with comprehensive climate models. Key Points: Simple energy balance models can build intuition for the climate system's response to solar radiation management, complementing global climate model studies The most effective latitudinal profile of insolation reduction depends on the intensity of the solar radiation modification intervention The effectiveness of solar radiation modification interventions depends on when they are applied not just how they are applied